Navigating the Psychological Safety Deficit : A Qualitative Exploration of Vietnamese Gen Z Workers' Experiences in the Workplace - Nguyen, Quynh Nguyen Huong; Honsová, Pavlína; Šilerová, Lenka, 1972-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This study investigates the barriers that hinder perceptions of psychological safety among Vietnamese Generation Z workers, providing a more comprehensive understanding of the potential consequences of this deficiency. The study highlights the urgent need to address psychological safety in the Vietnamese workplace context. By analyzing Hofstede’s cultural dimensions, workplace culture, and traditional cultural elements combining with intensive insights of Vietnamese young employees within the workplace context, this study seeks to understand the factors contributing to the lack of psychological safety among Vietnamese Gen Z workers. Semi-structured interviews were conducted in Ho Chi Minh City with a sample of interviewees aged 18 to 29 years from a broad spectrum of different positions and industries. The findings reveal six core themes affecting psychological safety: rigid hierarchical structures, cultural expectations and norms, lack of open communication channels, fear of judgment, generational conflict, and uncertainty about job stability. These barriers are closely linked to the Hofstede dimensions of power distance and collectivism, which further influence decision-making power, leadership styles, behavioral norms, and expectations in Vietnamese organizations. This research highlights the profound impact of these cultural factors on the experiences of Gen Z workers, urging targeted interventions to foster a supportive, productive, and psychologically safe work environment. The insights gained contribute to broader discussions on inclusion and psychological safety in the workplace environment, providing valuable implications for organizational practices in Vietnam and similar cultural contexts.
Vedoucí práce: Pavlína Honsová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses